Komunikasi Interpersonal dalam Mediasi Permasalahan Pasangan Suami Istri di Pengadilan Agama Banyuwangi - Ahmad Wafiudin; Kun Wazis (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
The divorce rate in Banyuwangi is very high. Efforts to mediate the problems of married couples so that divorce does not occur is an effort taken by mediators at the Banyuwangi Religious Court by using interpersonal communication in delivering messages to married couples. The focus of the study is as follows: 1) How is Interpersonal Communication in mediating husband and wife disputes at the Banyuwangi Religious Court?. 2) How does Interpersonal Communication overcome the Inhibiting factors in mediating marital disputes at the Banyuwangi Religious Court?. This study aims to find out how Interpersonal Communication is applied by mediators during mediation and what obstacles exist as well as solutions in Interpersonal Communication. This study uses a descriptive qualitative research approach and uses data collection techniques using interview techniques, observation documentation. The results showed: 1) Interpersonal communication in mediating the problems of married couples in the Banyuwangi Religious Court. The mediator has carried out his duties in the mediation process according to his function but the Interpersonal Communication that occurs in the Mediator with a husband and wife develops through the contact stage and stops at the involvement stage so there is little possibility to develop again to the next stage. 2) Interpersonal communication in overcoming the inhibiting factors in mediating husband and wife problems at the Banyuwangi Religious Court. here the barriers in question are cultural barriers, frame of mind, status, technical, psychological, sematic, and facility barriers.